“Come ve va de ingarellavve su sta cosa”: il romanesco di Strappare lungo i bordi e Questo mondo non mi renderà cattivo - Tolusso, Silvia (Studia Romanica Posnaniensia, 2024)
Regional language varieties and dialects are experiencing a period of enormous diffusion and of affirmation of the individuality of human beings: they are a comfort zone used to talk about everyday life, about one’s own intimacy, but also to build around oneself an identity fortress to be used in relationships with others. The close link between Roman dialect, territory and identity emerges in the two series Strappare lungo i bordi and Questo mondo non mi renderà cattivo, created by Zerocalcare. The contribution aims to analyze its language (above all, lexicon) and culture, to confirm how Roman dialect is a vehicle for representing identity.